2004
DOI: 10.1038/sj.pcan.4500734
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve and stage migration of a radical retropubic prostatectomy series over a 10-y period

Abstract: Objective: To show the impact of learning curve and patient selection on complication rate and biochemical recurrence-free survival of a UK radical prostatectomy series for localised prostate cancer and to model the influence of common preoperative variables on biochemical recurrence after controlling for learning curve. Patients and Methods: From 1989 to 1999, 280 of 350 patients who underwent anatomical radical retropubic prostatectomy (RRP) at our institution had complete records and follow-up of at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We know that outcome after RP in the UK is less optimistic compared to the often quoted large American series of RP. 4,10,11 This multicentre study assesses whether the age of English men undergoing RP is related to outcome (PSA recurrence-free survival). Such information would allow clinicians to counsel and select suitable candidates for RP irrespective of age.…”
Section: Discussionmentioning
confidence: 99%
“…We know that outcome after RP in the UK is less optimistic compared to the often quoted large American series of RP. 4,10,11 This multicentre study assesses whether the age of English men undergoing RP is related to outcome (PSA recurrence-free survival). Such information would allow clinicians to counsel and select suitable candidates for RP irrespective of age.…”
Section: Discussionmentioning
confidence: 99%
“…Direct supervision and practical experience are essential. Previous research has indicated that both the operative outcomes and complication rate may be directly related to experience of the surgeon 1,2 . In any training scheme, it is important to ensure that trainees are competent in performing a procedure before they are allowed to do it independently.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that both the operative outcomes and complication rate may be directly related to experience of the surgeon. 1,2 In any training scheme, it is important to ensure that trainees are competent in performing a procedure before they are allowed to do it independently. However, there is little quantitative information on the approximate number of particular operation a trainee should perform before they can be considered adequately skilled to perform the operation independently.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that there has been a significant stage migration towards lower clinical and pathological stages, resulting in large improvements in 5-year PSA recurrence-free survival after RP between 1998 and 2002. 7,8 Although there are many options available for those diagnosed with localised PCa, there is limited evidence to suggest outcomes are better with any single modality. A recent systematic review by Wilt et al concluded that there is not enough high-quality evidence to compare effectiveness and harms of treatments for clinically localised PCa.…”
Section: Introductionmentioning
confidence: 99%